How can economics contribute to environmental and social sustainability? The significance of systems theory and the embedded economy - Skene, Keith R. (Frontiers in Sustainability, 2022)
Concerns relating to resource extraction, manufacturing and waste in our supply chains and their consequences for the planet have re-focused the minds of government, business and consumers alike on the material world we continue to create. Parallel concerns circle around social and environmental resilience, recovery and sustainability. This paper seeks to explore what a sustainable economy should look like in order to contribute to a resilient, diverse and thriving planet, while furthering resilient, diverse and thriving communities. It is argued that at the centre of any sustainability theory, whether economic, environmental or social, lies the Earth system. The Earth system represents much more than the organisms sharing this planet with ourselves. Rather, it involves the fluxes of radiation, food energy, water, nutrients and heat. More essentially, it determines our niche space. Given that humans are some of the most vulnerable organisms on the planet in terms of the narrow range of conditions within which they can survive, the dynamic nature of the planet that determines these range of conditions must surely form the prime focus of our attentions. The Earth System, like all complex, far-from-equilibrium systems, is self-organising, self-assembling, emergent, nonlinear and governed by real-time feedback and sub-optimality at each level of its organization. The consequences of these properties for our economic activities and, indeed, for our own species, are discussed. It is further argued that we need an embedded economy. Fundamental to this exploration are the concept of zusammenhang (literally, hanging together), as developed by Humboldt, and the concept of the Earth as a super-organism, as developed by Hutton. Natural economics within the Earth system is explored and key properties of this economy are highlighted. The embedded economy functions in a way that facilitates environmental and social recovery, resilience and functionality, while in resonance with the key characteristics of the Earth system. Artificial intelligence, utilizing ecological intelligence rather than human intelligence, and the internet of things, are identified as potentially significant tools in the establishment of an embedded economy. The embedded economy is then compared and contrasted with current sustainable economics thinking, whose emphasis primarily focuses on resource cycling.